Reasoning in classroom dilemma situations: how pre-service teachers judge performance assessment - Greiner, Ulrike; Katstaller, Michaela; Oitner, Theresa (Frontiers in Education, 2024)
This study examines pre-service teachers’ reasoning structures based on their beliefs in the context of school performance assessment. We used reflective writing to investigate pre-service teachers’ judgment and reasoning regarding different functions of performance assessment. Forty-five undergraduate pre-service teachers participated in our study. Using a mixed-method approach, we conducted categorial and reconstructive text analyses as well as exploratory statistical analyses to describe the participants’ reasoning structures. Such cognitive structures comprise potential solutions to the performance assessment dilemmas that teachers face in their everyday teaching practice. We found varying distributions of and relationships between (individual-, objective-, social-, and ability-related) reference norms (neutral, student-, and teacher-centered) reference perspectives as well as (causal-analytic, normative, descriptive, and effect-oriented) modes of argumentation. Our discussions related to future research activities on teachers’ reasoning structures in the classroom.